Patent fundamentals for scientists and engineers - Gordon, Thomas T. (CRC Press, 2013)
"Ideal for anyone without prior legal knowledge who needs to understand the patent system, this book enables nonspecialists to make well-informed decisions affecting new and patentable products. The third edition covers the new patent law, the America Invents Act, which was recently passed by Congress and signed by the President. This is the first major change to the patent law in almost 60 years and is receiving a great deal of attention. The text provides a detailed analysis and description of the new patent law and how it will affect engineers. All chapters have been updated and include new sidebar case studies. A supporting website features videos and interviews that further explain the patent process"-- Provided by publisher.
Keywords: Patents.; Patents -- United States.; Patent laws and legislation.; Inventions.; elektronické knihy; electronic books